TI_GERICHTE 90.2011.77 vom 28. Juni 2013 , Revisione generale di un piano regolatore adottato e approvato in vigenza della LPT - TI Tribunale d'appello (2013)
Revisione generale di un piano regolatore adottato e approvato in vigenza della LPT